ANALISIS WAKTU TUNGGU PE/LAYANAN REKAM MEDIS DI POLI DALAM PENDAFTARAN RAWAT JALAN PADA MASA PANDEMI COVID DI RSUD PATUT PATUH PATJU KABUPATEN LOBAR TAHUN 2022 - Yulianti, Mega Sara; Yanti, Ni Komang Wijiani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
Patient waiting time is one indicator in assessing the quality of service in hospitals, if patient waiting time decreases it will affect the quality of service. The length of patient waiting time reflects how the hospital manages the service components that are tailored to the patient's situation and expectations. Based on a preliminary survey at the Patut Patuh Patju Hospital in 2021, the results obtained from the quality aspect of services, especially outpatient waiting times, only reached 50% of the assessment indicator achievements, which means there is a decrease in outpatient waiting times, in addition to patients who want to get outpatient services on average. The average person often complains that it is difficult to get a queue number, this is due to restrictions on the number of patients served during the Covid-19 pandemic. This study aims to determine the waiting time of outpatients during the Covid-19 pandemic. This research is a descriptive analytic study with a sampling technique using simple random sampling. Data were collected using observation sheets and interviews. Data processing uses editing, coding, data entry, cleaning and data analysis using quantitative analysis with descriptive statistics, frequency distribution of respondent characteristics variables (age, gender, education level, occupation, payment method), patient waiting time in medical record services, status patients, how to register patients, and human resources.